Translational Regulation of the Escherichia coli Stress Factor RpoS: a Role for SsrA and Lon - Ranquet, Caroline (American Society for Microbiology, 2007)
Escherichia coli cell viability during starvation is strongly dependent on the expression of the rpoS gene, encoding the RpoS sigma subunit of RNA polymerase. RpoS abundance has been reported to be regulated at many levels, including transcription initiation, translation, and protein stability. The regulatory RNA SsrA (or tmRNA) has both tRNA and mRNA activities, relieving ribosome stalling and cotranslationally tagging proteins. We report here that SsrA is needed for the correct high-level translation of RpoS. The ATP-dependent protease Lon was also found to negatively affect RpoS translation, but only at low temperature. We suggest that SsrA may indirectly improve RpoS translation by limiting ribosome stalling and depletion of some component of the translation machinery.